The Development of Biology Learning Module based on Brain Based Learning with Vee Diagram to Empowering the Science Process Skills and Self Regulation Ability - Valent Sari Danisa; Suciati Sudarisman; Widha Sunarno (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The objective of this developmental research is to know: 1) the procedure of the development of biology learning module based on Brain Based Learning with Vee Diagram; 2) the feasibility of biology learning module based on Brain Based Learning with Vee Diagram; and 3) the effectiveness of biology learning module based on Brain Based Learning with Vee Diagram to empowering the science process skills and self regulation ability. The method used in the research was Research and Development (R&D) refers to Borg & Gall model. The samples used in the research were early field trial sample consisting of 6 validators, main field trial sample consisted of 10 students even semester of the tenth grade at SMA Negeri 1 Ngemplak in academic year 2013/2014 and operational field trial sample consisted of 27 students even semester of the tenth grade at SMA Negeri 1 Banyudono in academic year 2013/2014. The instruments used in the research were questionnaire, observation, interview and test. The operational field trial used one group pretest-posttest design. The skill of science process and the ability of self-regulation data were tested by Wilcoxon test and counted by normalized gain. Based on the results of the research it can be concluded that: 1) the development of module uses Borg & Gall developmental; 2) the feasibility of module as good with value 3,45 by the expert, very good with value 3,79 by the practitioners and very good with value 3,63 by the students; and 3) the effectiveness of module is high categorized in empowering the science process skills with Ngain 0,72 as the significance of 0,000 and the self regulation ability with Ngain 0,71 as the significance of 0,000.Keywords: module development, brain based learning, vee diagram, science process skills, self regulation ability